Active composite membrane with asymmetric double-layer structure as well as preparation method and application of active composite membrane
An asymmetric bilayer active composite membrane constructed using chitosan, plant polyphenol crosslinking agents, and magnesium-based inorganic fillers solves the problems of insufficient mechanical strength, uncontrollable degradation, and insufficient antibacterial ability of bone regeneration guiding membranes under wet conditions, achieving highly efficient bone regeneration support and antibacterial effects.
Patent Information
- Application Number
- CN202511741138.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-24
- Publication Date
- 2026-01-16
AI Technical Summary
Existing bone regeneration guiding membranes lack mechanical strength in humid environments, are prone to collapse, have uncontrollable degradation rates, and lack antibacterial capabilities, making it difficult to effectively maintain bone regeneration space in complex bone defects.
An asymmetric bilayer active composite membrane was constructed using chitosan, plant polyphenol crosslinking agents, and magnesium-based biodegradable inorganic fillers. A ternary synergistic network was formed through covalent bonds, hydrogen bonds, and coordination bonds. A dense layer and a porous layer were prepared by combining solvent evaporation, rapid freeze-drying, and pre-cooling alkaline alcohol solution washing steps to ensure the structural stability and bioactivity of the membrane.
It achieves excellent tensile strength and tear resistance in wet conditions, has long-lasting antibacterial ability, promotes osteoblast proliferation and differentiation, and its degradation cycle matches the bone regeneration process, thus solving the problems of insufficient mechanical properties and limited biological activity of traditional membranes.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomedical materials technology, and in particular to an asymmetric bilayer active composite membrane, its preparation method, and its application. Background Technology
[0002] Guided bone regeneration (GBR) is a key strategy in dental implantology, maxillofacial surgery, and other fields for repairing critical-sized bone defects. Its core principle is to utilize a barrier membrane to create a physical barrier between the bone defect area and soft tissue, preventing the invasion of fibroblasts and epithelial cells and providing a dedicated regeneration space for osteoblasts. In the early clinical practice, non-absorbable guided bone regeneration membranes (ePTFE / dPTFE) were commonly used due to their good mechanical strength and space maintenance capabilities; however, they required a second surgery for removal and were prone to infection after exposure. Currently, the most widely used guided bone regeneration membrane in clinical practice is an absorbable collagen membrane composed of biodegradable polymers, with Geistlich's Bio-Gide® bilayer collagen membrane being a prime example. This membrane is derived from highly purified type I collagen and has a bilayer structure: a dense and smooth layer that acts as a physical barrier; and a loose and porous layer that facilitates blood clot stability and osteoblast attachment. Bio-Gide® membranes have excellent biocompatibility and biodegradability, avoiding the hassle of secondary surgical removal, and are therefore widely used in clinical practice.
[0003] However, with the increasing complexity of implant cases and the expansion of bone defect areas, these collagen membranes have gradually revealed many limitations: First, their mechanical strength decreases significantly in humid environments, resulting in insufficient tear and flexural resistance, making it difficult to resist soft tissue pressure at bone defects requiring significant space for maintenance, and prone to collapse; second, their degradation rate is greatly affected by individual differences and the local microenvironment, making precise control difficult, often leading to degradation that is too fast or too slow, causing premature failure of the barrier function or hindering new bone formation; furthermore, collagen membranes themselves lack antibacterial capabilities, making them prone to early exposure and infection in the complex oral microbial environment, and they do not possess the bioactivity to actively induce bone regeneration, only playing a passive isolation role. Therefore, an ideal guided bone regeneration membrane, in addition to possessing biocompatibility and a reasonable hierarchical structure, should also have stable structural support, reliable barrier function, and necessary functions (such as antibacterial, cell compatibility, and osteogenic friendliness). However, achieving this goal on the same membrane material while considering a mild and scalable manufacturing process and clinical operability remains extremely challenging.
[0004] To overcome the aforementioned defects of collagen membranes, researchers have turned their attention to chitosan-guided bone regeneration membranes. Chitosan (CS), a natural polysaccharide, possesses excellent biocompatibility, biodegradability, and intrinsic antibacterial properties. Once formed, its membranes typically exhibit superior mechanical strength and toughness compared to collagen membranes, better maintaining the space for bone regeneration. For example, Wu et al. significantly improved the rigidity and osteoconductivity of membranes by combining chitosan with hydroxyapatite (Nature Communications, 2024, 15:119). Furthermore, advanced fabrication techniques such as electrospinning have been used to construct asymmetric bilayer membranes with a Janus structure, achieving a gradient transition from a dense layer to a porous layer, balancing barrier function and cell invasion guidance (Advanced Functional Materials, 2025, 35:2423212). However, chitosan-based composite membranes still face a series of fundamental challenges: Yu et al. pointed out that many chitosan-based membranes lack flexibility in a wet state and are prone to brittle fracture, resulting in poor long-term stability (Matter, 2019, 1:770-781); in addition, most bilayer composite membranes suffer from interfacial discontinuity during preparation, with interlayer separation easily occurring between the dense and porous layers, which not only weakens the overall mechanical integrity but also provides channels for fibrous tissue invasion, ultimately leading to failure of guided bone regeneration (Nature Communications, 2025, 16:4264). In terms of functionality, although the osteogenic activity can be partially enhanced by adding inorganic particles or growth factors, their preparation process often involves multi-step crosslinking, high temperatures, or organic solvents, making the process cumbersome, costly, and difficult to scale up. Summary of the Invention
[0005] The present invention aims to at least solve one of the aforementioned technical problems existing in the prior art. Therefore, one objective of the present invention is to provide an asymmetric bilayer active composite membrane.
[0006] The second objective of this invention is to provide a method for preparing such an asymmetric bilayer active composite membrane.
[0007] The third objective of this invention is to provide applications of this asymmetric bilayer active composite membrane.
[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The first aspect of the present invention provides an asymmetric bilayer active composite membrane, comprising, by weight percentage, the following raw materials: Chitosan 95%-98%; Plant polyphenol crosslinking agent 0.5%-2%; Magnesium-based biodegradable inorganic fillers: 1%-4%. In some embodiments of the present invention, the asymmetric bilayer active composite membrane comprises the following raw materials by weight percentage: Chitosan 96%-98%; Plant polyphenol crosslinking agent 0.5%-1.5%; Magnesium-based biodegradable inorganic fillers: 1.5%-3%. In some embodiments of the present invention, the viscosity of the chitosan at 25°C is greater than or equal to 400 mPa·s.
[0009] In some preferred embodiments of the present invention, the viscosity of the chitosan at 25°C is 400-450 mPa·s.
[0010] In some embodiments of the present invention, the plant polyphenol crosslinking agent is selected from at least one of oxidized tannic acid and gallic acid.
[0011] In some preferred embodiments of the present invention, the plant polyphenol crosslinking agent is selected from oxidized tannins (OTA).
[0012] In some embodiments of the present invention, the particle size of the magnesium-based biodegradable inorganic filler is 10-100 nm.
[0013] In some preferred embodiments of the present invention, the particle size of the magnesium-based biodegradable inorganic filler is 30-50 nm.
[0014] In some embodiments of the present invention, the magnesium-based biodegradable inorganic filler is selected from at least one of magnesium oxide, magnesium hydroxide, and magnesium carbonate.
[0015] In some preferred embodiments of the present invention, the magnesium-based biodegradable inorganic filler is magnesium oxide (MgO).
[0016] A second aspect of the present invention provides a method for preparing the asymmetric bilayer active composite membrane described in the first aspect of the present invention, comprising the following steps: S1. Dissolve chitosan in acid to obtain solution A; dissolve plant polyphenol crosslinking agent in water to obtain solution B; disperse magnesium-based biodegradable inorganic filler in water to obtain dispersion C; S2. Add solution B and dispersion C to solution A, and adjust the pH to 5.0-7.0 to obtain a composite solution; S3. Divide the composite solution into a first part and a second part; firstly, evaporate and dry the first part of the solution to form a barrier layer; then apply the second part of the solution onto the barrier layer and freeze it with liquid nitrogen; S4. Wash the product from step S3 with a pre-cooled alkaline alcohol solution to obtain the asymmetric bilayer active composite membrane.
[0017] In some embodiments of the present invention, in step S1, the volume concentration of the acid solution is 0.8%-1.2%; and the mass-volume concentration of chitosan in solution A is 1.5%-2.5%.
[0018] In some preferred embodiments of the present invention, in step S1, the volume concentration of the acid solution is 0.9%-1.1%; and the mass-volume concentration of chitosan in solution A is 1.8%-2.3%.
[0019] In some embodiments of the present invention, in step S1, the acid solution is selected from at least one of acetic acid, citric acid, lactic acid, and hydrochloric acid.
[0020] In some preferred embodiments of the present invention, in step S1, the acid solution is acetic acid.
[0021] In some embodiments of the present invention, in step S1, the concentration of solution B is 0.8-1.2 mg / mL.
[0022] In some preferred embodiments of the present invention, in step S1, the concentration of solution B is 0.9-1.1 mg / mL.
[0023] In some embodiments of the present invention, in step S1, the concentration of the dispersion C is 3-5 mg / mL.
[0024] In some preferred embodiments of the present invention, in step S1, the concentration of the dispersion C is 3.5-4.5 mg / mL.
[0025] In some embodiments of the present invention, in step S2, the pH is adjusted to 5.5-6.5.
[0026] In some embodiments of the present invention, step S2 includes adding a pH adjuster to adjust the pH.
[0027] In some embodiments of the present invention, in step S2, the concentration of the pH adjuster is 120-180 mg / mL.
[0028] In some preferred embodiments of the present invention, in step S2, the concentration of the pH adjuster is 140-160 mg / mL.
[0029] In some embodiments of the present invention, in step S2, the solute of the pH adjuster is selected from at least one of potassium hydroxide and sodium hydroxide.
[0030] In some embodiments of the present invention, before dividing the composite solution into a first part and a second part in step S3, the composite solution is further subjected to ultrasonic degassing.
[0031] In some embodiments of the present invention, in step S3, the volume ratio of the first part of the solution and the second part of the solution is (2-3):1.
[0032] In some preferred embodiments of the present invention, in step S3, the volume ratio of the first part of the solution to the second part of the solution is (2.5-3):1.
[0033] In some embodiments of the present invention, in step S3, the thickness of the barrier layer is 25-35 μm.
[0034] In some embodiments of the present invention, in step S3, the solvent evaporation drying temperature is 30-40°C and the time is 20-35 hours.
[0035] In some preferred embodiments of the present invention, in step S3, the solvent evaporation drying temperature is 35-40°C and the time is 20-30 hours.
[0036] In some embodiments of the present invention, in step S3, the method of applying the second portion of the solution includes spraying or pouring.
[0037] In some embodiments of the present invention, in step S4, the concentration of the alkaline alcohol solution is 100-200 mg / mL.
[0038] In some preferred embodiments of the present invention, in step S4, the concentration of the alkaline alcohol solution is 140-160 mg / mL.
[0039] In some embodiments of the present invention, in step S4, the pre-cooling temperature of the alkaline alcohol solution is -30°C to -10°C.
[0040] In some preferred embodiments of the present invention, in step S4, the pre-cooling temperature of the alkaline alcohol solution is -25°C to -15°C.
[0041] In some embodiments of the present invention, in step S4, the alkaline alcohol solution comprises a sodium hydroxide / ethanol solution.
[0042] In some embodiments of the present invention, in step S4, the alkaline alcohol solution is washed 2-4 times.
[0043] In some embodiments of the present invention, step S4, after the alkaline alcohol solution washing is completed, also includes deionized water washing and freeze-drying.
[0044] The third aspect of the present invention provides the application of the asymmetric bilayer active composite membrane described in the first aspect of the present invention in the preparation of articles for bone defect repair.
[0045] The basic principles of this invention are explained as follows: 1) The asymmetric bilayer active composite membrane provided by this invention uses a chitosan matrix. The numerous amino and hydroxyl groups on the chitosan chains make it soluble in dilute acids for easy processing, and it can also form an initial physical cross-linking network through intermolecular hydrogen bonds, constituting the membrane's framework. Its cationic properties (positively charged under acidic conditions) allow it to adsorb onto the negatively charged bacterial cell walls, disrupting their metabolism and providing intrinsic antibacterial properties. The use of high-viscosity chitosan (viscosity ≥400 mPa·s at 25°C) ensures that the naturally formed chitosan film possesses good mechanical properties in both dry and wet conditions, and also ensures that the material will not rapidly degrade in vivo after film formation, thus meeting the needs of bone repair. The repair cycle; the catechol structure in the plant polyphenol crosslinking agent is oxidized to form a highly reactive o-quinone structure. This quinone group can undergo an irreversible Schiff base reaction with the amino group on the chitosan chain to form a strong C=N covalent bond, thereby greatly enhancing the stability of the polymer network and improving wet strength and tear resistance; the unoxidized phenolic hydroxyl groups in the molecule can form a dense hydrogen bond network with the amino and hydroxyl groups of chitosan. This physical crosslinking can effectively dissipate energy, giving the material better flexibility and resistance to deformation. The plant polyphenol crosslinking agent itself, as a plant polyphenol, also has antioxidant and synergistic antibacterial properties; the magnesium-based biodegradable inorganic filler produces Mg 2+ The phenolic hydroxyl groups of the plant polyphenol crosslinking agent can form a metal-phenol coordination network. Simultaneously, nanoscale magnesium-based biodegradable inorganic filler particles, uniformly dispersed within the chitosan network, act as physical crosslinking points, effectively hindering polymer chain slippage. The combined effect of these two factors significantly enhances the membrane's rigidity, anti-collapse ability, and structural stability. Furthermore, the magnesium-based biodegradable inorganic filler particles continuously release magnesium during degradation. 2+ and OH - It can neutralize the acidic products that may be produced by chitosan degradation, maintaining the local microenvironment in a weakly alkaline state favorable to osteoblasts, and releasing Mg 2+ It is an important osteogenic signaling factor that can directly promote the proliferation, differentiation and mineralization of osteoblasts. Chitosan, plant polyphenol crosslinking agent and magnesium-based biodegradable inorganic filler are combined with each other through covalent bonds, hydrogen bonds and coordination bonds to form a stable ternary synergistic network. This network ensures that the membrane can resist external forces (strength and toughness) and maintain structural integrity (anti-degradation and anti-delamination) in a moist in vivo environment. 2) An asymmetric bilayer active composite membrane was prepared using a process of solvent evaporation, rapid freeze-drying, and pre-cooling alkaline alcohol solution washing: First, a portion of the chitosan / plant polyphenol crosslinking agent / magnesium-based biodegradable inorganic filler composite solution was slowly evaporated to remove the solvent. As the solvent evaporated, the solution concentration continuously increased. Under the fixation of the crosslinking network (plant polyphenol crosslinking agent, magnesium-based biodegradable inorganic filler), the polymer chains (chitosan) were forced to approach each other and densely pack together, ultimately forming a smooth, dense layer with highly entangled molecular chains and extremely low porosity, which played a major role in physically blocking fibroblasts. The same solution was then applied to the formed dense layer and rapidly frozen with liquid nitrogen. This process caused the water in the solution to instantly form tiny ice crystals. These ice crystals repelled the polymer chains and filler into the gaps between the ice crystals. Subsequently, under vacuum and low-temperature conditions… Ice crystals sublimate directly into water vapor and are removed, leaving behind interconnected three-dimensional porous structures in the spaces previously occupied by ice crystals. This provides an ideal channel for osteoblast attachment, proliferation, migration, and the transport of nutrients and metabolic waste. Pre-cooling alkaline alcohol washing first neutralizes residual acetic acid in the system, deprotonating the chitosan amino groups and changing them from a soluble to an insoluble state, thus permanently solidifying the entire network. As a non-solvent, alcohol can also induce further aggregation and precipitation of polymer chains, strengthening the network. Pre-cooling ensures that the ice crystal template of the porous layer does not melt during the process, thus perfectly preserving the porous structure created by the freezing step. Through washing, the newly formed porous layer and the underlying dense layer are interconnected and tightly bonded at the molecular chain level, eliminating obvious interfaces and solving the problem of easy delamination in traditional bilayer membranes.
[0046] Compared with the prior art, the beneficial effects of the present invention are: 1) The active composite membrane provided by this invention has an integrated double-layer structure with no interface bonding. The dense layer can effectively block soft tissue, while the porous layer facilitates cell adhesion and nutrient transport. The covalent-non-covalent-coordination triple synergistic network constructed by chitosan, plant polyphenol crosslinking agent, and magnesium-based biodegradable inorganic filler gives the membrane excellent tensile strength, tear resistance, and collapse resistance in a wet state. At the same time, the membrane integrates a triple long-term antibacterial mechanism of cationic chitosan antibacterial, polyphenol crosslinking agent antibacterial, and magnesium-based biodegradable inorganic filler in a slightly alkaline environment, which can effectively inhibit the growth and reproduction of bacteria such as Escherichia coli and Staphylococcus aureus. The membrane is non-cytotoxic, has high cell compatibility, and can continuously release Mg 2+ Actively regulating the local microenvironment to a weakly alkaline state significantly promotes osteoblast proliferation and differentiation; the enhanced cross-linking network also enables the degradation cycle to be well matched with the bone regeneration process, solving the defects of traditional guided bone regeneration membranes in terms of insufficient mechanical properties, uncontrollable degradation, lack of biological activity and limited antibacterial ability under wet conditions.
[0047] 2) The method for preparing the asymmetric bilayer active composite membrane provided by the present invention adopts the steps of solvent evaporation-rapid freeze drying-pre-cooling alkaline alcohol solution washing. The entire preparation process is carried out in the aqueous phase, with mild conditions, simple steps and no need for complex equipment, showing extremely high potential for clinical translation and industrialization. Attached Figure Description
[0048] Figure 1 Photograph (a) and cross-sectional scanning electron microscope image (b) of the asymmetric bilayer active composite membrane in Example 1; Figure 2 The images show scanning electron microscope (SEM) images of the barrier layer (a) and porous layer (b) of the asymmetric bilayer active composite membrane in Example 1. Figure 3 The tensile stress-strain curves of the active composite membranes in Example 1, Comparative Example 1, and Comparative Example 2 under typical wet conditions are shown. Figure 4 The results of the cell compatibility evaluation of the active composite membranes in Example 1, Comparative Example 1, and Comparative Example 2 are shown. Figure 5 The bacterial growth curves are those of the active composite membranes co-cultured with Escherichia coli in Example 1, Comparative Example 1, and Comparative Example 2. Figure 6 The bacterial growth curves are those obtained by co-culturing the active composite membrane with Staphylococcus aureus in Example 1, Comparative Example 1, and Comparative Example 2. Figure 7 The degradation mass loss curves of the active composite membranes in Example 1, Comparative Example 1, and Comparative Example 2 are shown. Detailed Implementation
[0049] The present invention will be further described in detail below through specific embodiments. Unless otherwise specified, the raw materials, reagents, or apparatus used in the embodiments and comparative examples are all available from conventional commercial sources or can be obtained by existing technical methods. Unless otherwise specified, the test or experimental methods are conventional methods in the art.
[0050] Example 1 This embodiment prepares an asymmetric bilayer active composite membrane, and the steps are as follows: S11. Put 0.5g of chitosan powder (viscosity of 400mPa·s at 25℃) into a 100mL beaker, and add 1% (v / v) acetic acid solution to prepare a chitosan concentration of 2% (w / v) solution A. S12. Dissolve 0.005g of oxidized tannic acid in water to prepare solution B with a concentration of 1mg / mL; S13. Disperse 0.015g of magnesium oxide (particle size 30-50nm) in water to prepare a dispersion C with a concentration of 4mg / mL; S21. Add solution B and dispersion C to solution A, and adjust the pH to 6.0 with 150 mg / mL NaOH solution to obtain a composite solution; S31. After removing air bubbles from the composite solution by ultrasonication, it is divided into a first part (30 mL) and a second part (10 mL). The first part of the solution is poured into a 10 cm petri dish and dried in an oven at 37°C for 24 h to form a barrier layer with a thickness of about 30 μm. S32. Spray the second part of the solution onto the dense barrier layer and quickly freeze it with liquid nitrogen; S41. Dissolve 15g NaOH in 100mL of anhydrous ethanol to prepare a NaOH / ethanol solution with a concentration of 150mg / mL, and pre-cool it at -20℃. S42. Wash the product from step S32 three times with pre-cooled NaOH / ethanol solution, and wash with deionized water to remove excess impurities. Finally, freeze-dry for three days to obtain an asymmetric bilayer active composite membrane, denoted as CS / OTA / MgO.
[0051] Example 2 This embodiment prepares an asymmetric bilayer active composite membrane, and the steps are as follows: S11. Put 2.0g of chitosan powder (viscosity of 450mPa·s at 25℃) into a 100mL beaker, and add 1% (v / v) acetic acid solution to prepare a chitosan solution A with a concentration of 2% (w / v). S12. Dissolve 0.01g of gallic acid in water to prepare solution B with a concentration of 1mg / mL; S13. Disperse 0.03g of magnesium hydroxide (particle size 30-50nm) in water to prepare a dispersion C with a concentration of 4mg / mL; S21. Add solution B and dispersion C to solution A, adjust the pH to 6.0 with 150 mg / mL NaOH solution to obtain a composite solution, and mix the solutions. S31. After removing air bubbles from the composite solution by ultrasonication, it is divided into a first part (25 mL) and a second part (10 mL). The first part of the solution is poured into a 10 cm culture dish and dried in an oven at 37°C for 24 h to form a barrier layer. S32. Spray the second part of the solution onto the dense barrier layer and quickly freeze it with liquid nitrogen; S41. Dissolve 15g NaOH in 100mL of anhydrous ethanol to prepare a NaOH / ethanol solution with a concentration of 150mg / mL, and pre-cool it at -20℃. S42. Wash the product from step S32 three times with pre-cooled NaOH / ethanol solution, and wash with deionized water to remove excess impurities. Finally, freeze-dry for three days to obtain an asymmetric bilayer active composite membrane, denoted as CS / GA / Mg(OH)2.
[0052] Comparative Example 1 This comparative example prepares an asymmetric bilayer active composite membrane, and the steps are as follows: S11. Put 0.5g of chitosan powder (viscosity of 400mPa·s at 25℃) into a 100mL beaker, and add 1% (v / v) acetic acid solution to prepare a chitosan concentration of 2% (w / v) solution A. S31. After removing air bubbles from solution A by sonication, divide it into a first part (30 mL) and a second part (10 mL). Pour the first part of the solution into a 10 cm culture dish and dry it in an oven at 37°C for 24 h to form a barrier layer with a thickness of about 30 μm. S32. Spray the second part of the solution onto the dense barrier layer and quickly freeze it with liquid nitrogen; S41. Dissolve 15g NaOH in 100mL of anhydrous ethanol to prepare a NaOH / ethanol solution with a concentration of 150mg / mL, and pre-cool it at -20℃. S42. Wash the product from step S32 three times with pre-cooled NaOH / ethanol solution, and wash with deionized water to remove excess impurities. Finally, freeze-dry for three days to obtain an asymmetric bilayer active composite membrane, denoted as CS.
[0053] Comparative Example 2 This comparative example prepares an asymmetric bilayer active composite membrane, and the steps are as follows: S11. Put 0.5g of chitosan powder (viscosity of 400mPa·s at 25℃) into a 100mL beaker, and add 1% (v / v) acetic acid solution to prepare a chitosan concentration of 2% (w / v) solution A. S12. Dissolve 0.005g of oxidized tannic acid in water to prepare solution B with a concentration of 1mg / mL; S21. Add solution B to solution A, and adjust the pH to 6.0 with 150 mg / mL NaOH solution to obtain a composite solution; S31. After removing air bubbles from the composite solution by ultrasonication, it is divided into a first part (30 mL) and a second part (10 mL). The first part of the solution is poured into a 10 cm petri dish and dried in an oven at 37°C for 24 h to form a barrier layer with a thickness of about 30 μm. S32. Spray the second part of the solution onto the dense barrier layer and quickly freeze it with liquid nitrogen; S41. Dissolve 15g NaOH in 100mL of anhydrous ethanol to prepare a NaOH / ethanol solution with a concentration of 150mg / mL, and pre-cool it at -20℃. S42. Wash the product from step S32 three times with pre-cooled NaOH / ethanol solution, and wash with deionized water to remove excess impurities. Finally, freeze-dry for three days to obtain an asymmetric bilayer active composite membrane, denoted as CS / OTA.
[0054] 1. The asymmetric bilayer active composite film prepared in Example 1 was characterized by scanning electron microscopy: Figure 1 The images shown are a photograph (a) and a cross-sectional scanning electron microscope (SEM) image (b) of the asymmetric bilayer active composite membrane in Example 1. Figure 1 It can be seen that the active composite membrane prepared in Example 1 has an integrated asymmetric bilayer structure, with a porous layer at the bottom and a dense barrier layer at the top, and there is no obvious physical interface between the two layers. Figure 2 These are scanning electron microscope (SEM) images of the barrier layer (a) and porous layer (b) of the asymmetric bilayer active composite membrane in Example 1. Figure 2 As can be seen, the asymmetric bilayer active composite membrane prepared in Example 1 has a barrier layer that is smooth, dense, and without visible pores. This provides a morphological basis for its function of blocking fibroblasts. The porous layer, on the other hand, has an open and interconnected three-dimensional porous structure. The size and connectivity of the pores directly affect the migration, nutrient delivery, and blood vessel ingrowth of osteoblasts.
[0055] 2. The mechanical properties of the asymmetric bilayer active composite membranes prepared in Example 1, Comparative Example 1, and Comparative Example 2 were tested under simulated body fluid conditions, as follows: The tensile test of the membrane was carried out on an Instron 5565A system with a 500-N load cell. The active composite membrane sample was cut into strips 50 mm long and 3 mm wide. Before the test, it was placed in a constant temperature and humidity chamber (25°C, 50% relative humidity) for 24 hours. Then it was taken out and tested immediately. The test was carried out at a load rate of 1 mm / min and a gauge length of 5 mm.
[0056] Figure 3 The figures show the tensile stress-strain curves of the active composite membranes in Example 1, Comparative Example 1, and Comparative Example 2 under typical wet conditions. The difference between Comparative Example 1 and Example 1 is the absence of the plant polyphenol crosslinking agent oxidized tannin and the magnesium-based biodegradable inorganic filler magnesium oxide. The difference between Comparative Example 2 and Example 1 is the absence of the magnesium-based biodegradable inorganic filler magnesium oxide. Figure 3It can be seen that the mechanical properties of Example 1, Comparative Example 1 and Comparative Example 2 under wet conditions show the trend of Example 1 > Comparative Example 2 > Comparative Example 1. This indicates that the pure CS membrane in Comparative Example 1 has poor wet mechanical properties. The introduction of oxidized tannic acid in Comparative Example 2 enhances the strength and toughness of the material through crosslinking. In Example 1, the synergistic effect of magnesium oxide nanoparticles and OTA / CS network brings the best wet mechanical properties, which makes the asymmetric bilayer active composite membrane exhibit excellent elongation at break (140%) and tensile strength (about 9 MPa) under wet conditions.
[0057] 3. Quantitative analysis of cell activity was performed on the active composite membranes prepared in Example 1, Comparative Example 1, and Comparative Example 2. The tests were conducted in accordance with GB / T 16886.1-2022 "Biological Evaluation of Medical Devices Part 1: Evaluation and Testing in Risk Management Processes", specifically as follows: The active composite membranes were perforated to form uniform discs with a diameter of 6 mm, and then sterilized using an autoclave (HVE-50, Pingshan). The membrane samples were divided into two groups and placed in two 96-well plates. Human bone marrow mesenchymal stem cells (hBMSCs) were seeded into these wells and incubated in DMEM medium supplemented with 10% FBS and 1% penicillin / streptomycin at 37°C in a humidified atmosphere of 5% CO2. On days 1, 3, and 7 of incubation, CCK-8 reagent and α-MEM were mixed at a volume ratio of 1:10, and 110 μL of the mixture was added to each well. The cells were cultured at 37°C for another 2 h. Finally, the samples were removed, and the number of viable cells was measured using a microplate reader at a wavelength of 450 nm (n=4, where n represents the number of wells in each active composite membrane).
[0058] Figure 4 The results of the cell compatibility evaluation of the active composite membranes in Example 1, Comparative Example 1, and Comparative Example 2 are provided by [the relevant authority / organization]. Figure 4 It can be seen that, at different culture times, the cell activity of the active composite membranes in Comparative Examples 1 and 2 was not significantly different from that of the blank group, proving that the material is non-cytotoxic and has high cell compatibility. The cell activity of the asymmetric bilayer active composite membrane in Example 1 was significantly higher than that of the blank group, indicating that the composite membrane in Example 1 is not only non-cytotoxic, but also can pass through Mg 2+ It promotes cell proliferation.
[0059] 4. The antibacterial properties of the active composite membranes prepared in Example 1, Comparative Example 1, and Comparative Example 2 were tested. The tests were conducted according to the basic principles of ISO 10993 series standards WS / T 650-2019 "Evaluation Methods for Antibacterial and Bacteriostatic Effects". Staphylococcus aureus (ATCC 25923) and Escherichia coli (ATCC 25922) were used to evaluate the antibacterial activity of the active composite membranes. The antibacterial properties were determined by the OD value, as detailed below: Dilute all bacterial suspensions to 10 5 CFU / mL, different active composite membranes were flushed into uniform disks with a diameter of 6 mm, and then sterilized using an autoclave (HVE-50, Hirayama, Japan). The sterilized membrane samples were placed at the bottom of a 96-well plate, and 150 μL of bacterial suspension was added to each well and incubated for 24 h (n=3, where n represents the number of wells in the plate for each active composite membrane). Finally, the samples were removed and the absorbance at 600 nm was measured using an automated microplate reader (MQX200, Bio-Rad, USA).
[0060] Figure 5 The figures show the bacterial growth curves of the active composite membranes co-cultured with *E. coli* in Examples 1, 1, and 2. Figure 6 The figures show the bacterial growth curves of the active composite membranes co-cultured with Staphylococcus aureus in Examples 1, 1, and 2. Figure 5 and Figure 6 It can be seen that the bacteria in the blank control group all grew normally, and the OD value rose rapidly and entered the plateau phase. In Comparative Example 1, due to the intrinsic antibacterial properties of chitosan, its growth curve was lower than that of the blank group. In Comparative Example 2, due to the synergistic antibacterial effect of oxidized tannins, its antibacterial effect was better than that of Comparative Example 1. In Example 1, the asymmetric bilayer structure active composite membrane showed the strongest antibacterial effect and the flattest growth curve, which proved the effectiveness of the CS-OTA-MgO triple antibacterial system.
[0061] 5. The active composite membranes prepared in Example 1, Comparative Example 1, and Comparative Example 2 were subjected to in vitro degradation tests, as follows: Several 1cm*1cm samples of the active composite membrane were prepared, dried, and randomly divided into 12 groups (n=3) and numbered. The weight of each membrane was recorded as m0 (0.1 ± 0.001g). Each membrane was placed in a 37℃ shaking incubator containing 1.5μg / mL lysozyme (egg white source, Sigma) and immersed in 30mL PBS buffer (pH=7.4). The culture medium was changed every two days to maintain enzyme activity. One group of samples was selected weekly, rinsed with deionized water to remove residual salt and enzyme, weighed, and dried in an oven. The value was recorded as m1. The control group without lysozyme was cultured under the same conditions. The mass retention rate at a specific time point was calculated using the following formula: Mass retention rate (%) = (m1 / m0) × 100%.
[0062] Figure 7 The degradation mass loss curves of the active composite membranes in Example 1, Comparative Example 1, and Comparative Example 2 are shown below. Figure 7It can be seen that the active composite membranes of Example 1, Comparative Example 1 and Comparative Example 2 can all continuously degrade. Among them, the active composite membrane in Comparative Example 1 degrades the fastest because the pure CS membrane lacks a tight cross-linking network. The active composite membrane in Comparative Example 2 degrades at a slower rate than that in Comparative Example 1, indicating that the cross-linking of oxidized tannic acid plays a role in delaying degradation. The asymmetric bilayer active composite membrane in Example 1 degrades the slowest, which shows that the introduction of magnesium oxide further stabilizes the network structure and achieves controllability of the degradation cycle.
Claims
1. An asymmetric bilayer active composite membrane, characterized in that, The following raw materials are included by weight percentage: Chitosan 95%-98%; Plant polyphenol crosslinking agent 0.5%-2%; Magnesium-based biodegradable inorganic fillers: 1%-4%.
2. The asymmetric bilayer active composite membrane according to claim 1, characterized in that, The viscosity of the chitosan at 25°C is greater than or equal to 400 mPa·s.
3. The asymmetric bilayer active composite membrane according to claim 1, characterized in that, The plant polyphenol crosslinking agent is selected from at least one of oxidized tannic acid and gallic acid.
4. The asymmetric bilayer active composite membrane according to claim 1, characterized in that, The magnesium-based biodegradable inorganic filler has a particle size of 10-100 nm.
5. The asymmetric bilayer active composite membrane according to claim 4, characterized in that, The magnesium-based biodegradable inorganic filler is selected from at least one of magnesium oxide, magnesium hydroxide, and magnesium carbonate.
6. The method for preparing the asymmetric bilayer active composite membrane according to any one of claims 1-5, characterized in that, Includes the following steps: S1. Dissolve chitosan in acid to obtain solution A; dissolve plant polyphenol crosslinking agent in water to obtain solution B; disperse magnesium-based biodegradable inorganic filler in water to obtain dispersion C; S2. Add solution B and dispersion C to solution A, and adjust the pH to 5.0-7.0 to obtain a composite solution; S3. Divide the composite solution into a first part and a second part; firstly, evaporate and dry the first part of the solution to form a barrier layer; The second portion of the solution is then applied to the barrier layer and sealed with liquid nitrogen. S4. Wash the product from step S3 with a pre-cooled alkaline alcohol solution to obtain the asymmetric bilayer active composite membrane.
7. The preparation method according to claim 6, characterized in that, In step S1, the volume concentration of the acid solution is 0.8%-1.2%; the mass-volume concentration of chitosan in solution A is 1.5%-2.5%. And / or, the concentration of solution B is 0.8-1.2 mg / mL; And / or, the concentration of the dispersion C is 3-5 mg / mL.
8. The preparation method according to claim 6, characterized in that, In step S3, the volume ratio of the first part of the solution to the second part of the solution is (2-3): 1; And / or, the solvent is evaporated and dried at a temperature of 30-40°C for 20-35 hours.
9. The preparation method according to claim 6, characterized in that, In step S4, the concentration of the alkaline alcohol solution is 100-200 mg / mL; And / or, the pre-cooling temperature of the alkaline alcohol solution is -30°C to -10°C.
10. The use of the asymmetric bilayer active composite membrane according to any one of claims 1-5 in the preparation of articles for bone defect repair.
Citation Information
Cited By
Double-layer guided bone regeneration membrane and preparation method thereof
CN121754741A
